Peningkatan Pemahaman Peserta Didik Pada Mata Pelajaran PAI Fase E Melalui Alat Asesmen Berbantuan Quizizz - Anly Maria; Ai Linda (MASAGI : Jurnal Pendidikan Agama Islam, 2026)
Education is a process of shaping behavior and ethics toward a better life, while morality reflects the character within a person’s soul. Instilling morality from an early age is very important due to the increasing number of rule violations among students, whether in attitudes, speech, or actions that are inconsistent with moral values. At SMK Ma’arif Sukawening Garut, students’ understanding of the material “Commendable Morals and Reprehensible Morals” was still low, reaching only 40.6% in the pre-cycle stage. This condition indicates the need for more innovative learning strategies to improve students’ comprehension. This study aims to describe the improvement of students’ understanding of the material in PAI subjects through assessments assisted by the Quizizz application in phase E. The research employed Classroom Action Research (CAR) with qualitative and quantitative approaches, including planning, implementation, observation, and reflection. Quantitative data were collected through learning achievement tests, while qualitative data were obtained from observations, interviews, and documentation to strengthen the findings. The results showed an increase in students’ understanding from 40.6% in the pre-cycle (fair category), to 71.9% in cycle I (good category), and 91.6% in cycle II (very good category). Thus, there was a significant improvement of 51%. Quizizz-based assessments proved highly effective in enhancing students’ understanding, motivation, and engagement in learning morals.  Keywords: quizizz assessment, students’ understanding, islamic religious education